Evaluation of Association Between the Serum Levels of MMP-9 and MMP-9/TIMPs With Soluble Forms of Selectins and Itching Induced by Sulfur Mustard - Nayere Askari; Tooba Ghazanfari; Mohammad Mehdi Naghizadeh; Athar Moin; Ali Khamesipour; Shahryar Pourfarzam; Zuhair Mohammad Hassan (Iranian Society of Pathology, 2017)
Background & objective: Pruritus is the most frequent chronic dermal complication of sulfur mustard (SM), which negatively influences the quality of life. Exact pathophysiology of SM-induced itching is unknown. The current study aimed at evaluating the possible association between SM-induced itching and the serum levels of matrix metalloproteinase (MMP)-9 and their endogenous inhibitors, and serum levels of soluble forms of selectins (sL-, sP-, and sE-selectins) as adhesion molecules involved in the development of different inflammatory reactions. Methods: Serum levels of MMP-9, MMP-9/ tissue inhibitors of metalloproteinases (TIMPs), and selectins were measured by the enzyme-linked immunosorbent assay (ELISA), and compared between the groups (n=368) with and without itching, and matched control groups (n=126). Results: Serum levels of MMP-9 were significantly higher in the SM exposed group with itching, compared with that of the group without itching (medians: 894 and 624 pg/mL respectively; P-value =0.034). There was no relationship between the serum levels of MMP-9/TIMP-1, MMP-9/TIMP-2, MMP-9/TIMP-4, and itching in the patients exposed to SM. Median serum levels of sE- and sL-selectins in the exposed group with itching were higher than those of the exposed group without itching. These differences were statistically insigniﬁcant (P-values =0.084 and 0.095, respectively). Conclusion: According to the results of the current study, the increased serum levels of MMP-9 and selectins 20 years after exposure may play role in the pathogenesis and persistence of SM-induced itching in the exposed individuals.